Experimental evidence of structural representation of hands in early infancy. (January 2019) - Jubran, Rachel; White, Hannah; Chroust, Alyson; Heck, Alison; Bhatt, Ramesh S.
Hands convey important social information, such as an individual's emotions, goals, and desires, are used to direct attention through pointing, and are a major organ for haptic perception. However, very little is known about infants' representation of human hands. In Experiment 1, infants tested in a familiarization/novelty preference task discriminated between images of intact hands and images that contained first-order structure distortions (i.e., with locations of fingers altered to result in an unnatural configuration). In Experiment 2, infants tested in a spontaneous preference task exhibited a preference for scrambled hand images over intact images, indicating that 3.5-month-olds have gained sufficient sensitivity to the configural properties of hands to discriminate between intact versus scrambled images without any training in the laboratory. In both procedures, infants' performance was disrupted by the inversion of images, suggesting that infants' performance in upright conditions was not based on low-level features. These results indicate that sensitivity to the structure of hands develops early in life. This may lay the foundation for the development of the functional use of hand information for social communication.